Synthesis, Characterization, and Antimicrobial Activities of Coordination Compounds of Aspartic Acid - T. O. Aiyelabola; D. A. Isabirye; E. O. Akinkunmi; O. A. Ogunkunle; I. A. O. Ojo (Journal of Chemistry)
Coordination compounds of aspartic acid were synthesized in basic and acidic media, with metal ligand M : L stoichiometric ratio 1 : 2. The complexes were characterized using infrared, electronic and magnetic susceptibility measurements, and mass spectrometry. Antimicrobial activity of the compounds was determined against three Gram-positive and three Gram-negative bacteria and one fungus. The results obtained indicated that the availability of donor atoms used for coordination was a function of the pH of the solution in which the reaction was carried out. This resulted in varying geometrical structures for the complexes. The compounds exhibited a broad spectrum of activity and in some cases better activity than the standard.